Myopathy: As an Initial Presentation of Hypothyroidism in Two cases of Autoimmune Thyroiditis (Journal of Medicine, 2008)
Although hypothyroidism may cause a wide range of muscle disturbances, an overt myopathy may rarely present as an isolated initial presentation of hypothyroidism. The frequency of myopathy in hypothyroidism ranges from 30 to 80%. The major muscular symptoms are weakness, muscular cramps and myalgia. Laboratorial investigation generally shows increased levels of muscle enzymes and low serum thyroid hormones, with high thyrotrophic-stimulating hormone (TSH) elevated. The electrophysiological study reveals myopathy, neuropathy or mixed pattern. The treatment consists in hormone replacement and the prognosis is good in most of the cases. We report two cases that developed cramps, myalgia, and weakness, one of them presented as a polymyositis-like syndrome. The muscle enzymes were increased with a raised level of TSH. The myopathy was the initial manifestation of hypothyroidism in these cases. Both the patient was treated by replacement of thyroxin with significant clinical and biochemical improvement. DOI = 10.3329/jom.v8i1.1379 J MEDICINE 2007; 8 : 32-36